1984
DOI: 10.1159/000466261
|View full text |Cite
|
Sign up to set email alerts
|

Viral Hepatitis Markers in Thai Blood Donors

Abstract: 1,410 voluntary blood donors from Bangkok were investigated by radioimmunoassay for HBsAg, anti-HBs, anti-HBc, HBeAg, anti-HBe and anti-HAV. An HBsAg carrier state was observed in 10.7% of whom 42.1% were HBeAg positive and 40.2% had anti-HBe. Antibody prevalences (except anti-HBe) rose with increasing age. The occurrence of hepatitis markers did not vary significantly between donors living along the canals and those living in the Greater Bangkok area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Same as in other populations in Asia (Seidi et al, 1984;Ishida et al, 2002), HBV was found in two of the three groups with rather high prevalence rates. Because of the small sample size, the negativity of HBV in the Chepang group studied here does not rule out the possible presence of HBV in other Chepang groups; a further epide miologicalstudy is necessary.…”
Section: Resultssupporting
confidence: 67%
“…Same as in other populations in Asia (Seidi et al, 1984;Ishida et al, 2002), HBV was found in two of the three groups with rather high prevalence rates. Because of the small sample size, the negativity of HBV in the Chepang group studied here does not rule out the possible presence of HBV in other Chepang groups; a further epide miologicalstudy is necessary.…”
Section: Resultssupporting
confidence: 67%